Public Representations of Immigrants in Museums Exhibition and Exposure in France and Germany - Porsché, Yannik (Postdisciplinary Studies in Discourse, 2018)
This book offers an interactionist perspective on theories of public representation, knowledge and immigration in museum institutions. Examining how a Franco-German museum exhibition represents immigrants and exposes public stereotypes, the analysis follows the process of the production and reception of the exhibition as it travelled from Paris to Berlin. The author proposes a microsociological contextualisation analysis integrating discourse analysis and ethnography to compare formats of museum work, social interaction in the exhibition and mass media debates. Visitor reception of the different exhibition versions reveal the symbolic nature of interactions in museums, for example concerning conflicting political voices and accusations of censorship. Depending on the institutional context, interactions in the museums are geared towards securing immigrants a place in national collective memory, towards carrying out debate on integration, or providing opportunities for personal encounters and reflection beyond national categorisation. This book will appeal to students and researchers interested in work on the intersection of sociology, cultural studies, and discursive psychology, in methods of discourse analysis and ethnography; and to practitioners working in museums.